A perfect chemistry photographs by Hill & Adamson - Lyden, Anne M. 1972- (National Galleries of Scotland, 2017)
Pioneering Edinburgh photographers David Octavius Hill (1802-1870) and Robert Adamson (1821-1848) together formed one of the most famous partnerships in the history of photography. Producing highly skilled photographs just four years after the new medium was announced to the world in 1839, their images of people, buildings and scenes in and around Edinburgh offer a fascinating glimpse into 1840s Scotland. Their much-loved prints of the Newhaven fisherfolk are among the first images of social documentary photography.In the space of four and a half years Hill and Adamson produced several thousand prints encompassing landscapes, architectural views, tableaux vivants from Scottish literature and an impressive suite of portraits featuring key members of Edinburgh society.00Exhibition: Scottish National Portrait Gallery, Edinburgh, Scotland (27.03. - 01.10.2017)
Keywords: Hill, David Octavius -- 1802-1870; Adamson, Robert -- 1821-1848; Geschichte 1845-1847; Fotografie; Ausstellungskatalog -- Scottish National Portrait Gallery -- 27.05.2017-01.10.2017 -- Edinburg